Criteria and leveling characteristics of the cognitive activity of students in higher educational institutions (Pedagogy of Higher and Secondary Education, 2012)
Chuvasova N. Criteria and leveling characteristics of the cognitive activity of students in higher educational institutions.In the article the exposed criteria and level descriptions of cognitive activity of students of higher pedagogical establishments and ways and methods of decision of problem of determination of level of formed of cognitive activity of students are examined.
Keywords: cognitive activity; criteria; structural components of cognitive activity; levels of formed of cognitive activity of students